Respiratory viral panels and pediatric airway evaluation: The role of testing for upper respiratory infections to stratify perioperative risk. (July 2020) - Niermeyer, Weston L.; Ball, Jessica; Worobetz, Noah; Bourgeois, Tran; Onwuka, Amanda; Burrier, Candice; Chiang, Tendy
Abstract: Objectives: Children admitted with stridor and respiratory distress comprise a complex patient group that requires the otolaryngologist to decide when to assess and intervene with direct laryngoscopy and bronchoscopy (DLB). Historically, the diagnosis of viral upper respiratory tract infection (URTI) can lead to postponement of surgery due to concerns of perioperative complications related to acute illness. Respiratory viral panels (RVP) are often used to confirm the presence of recent or active viral infection and can affect the differential diagnosis of upper airway obstruction. This study examined whether positive RVP testing is associated with perioperative complications and operative findings in pediatric patients undergoing inpatient DLB. Methods: A retrospective chart review of 132 pediatric patient encounters was performed. Viral testing results, DLB indication, DLB findings, and perioperative complications were compared. Results: Sixty encounters (45.5%) involved a positive RVP, and 72 (54.5%) involved a negative RVP. Those with positive RVP were less likely to have a preoperative structural airway diagnosis ( P =.0250) and more likely to have a history of recurrent upper respiratory infections ( P =.0464). The most common reason for DLB was the need to assess the airway due to concern for structural pathology. Anatomic abnormalities were seen in a majority of encounters (77.3%) Laryngospasm occurred in 1 (1.7%) RVP positive and 1 (1.4%) RVP negative encounter, and 2 (2.8%) RVP negative encounters required reintubation. No other major complications were observed. No association was noted between RVP results and incidence of major or minor complication. Conclusions: Major perioperative complications after surgical intervention with DLB for the management of complex, inpatient children with stridor and respiratory distress are rare. RVP positivity, specific pathogens identified on RVP, and presence of URI symptoms were not associated with perioperative complications.